2008
DOI: 10.1007/s00330-008-1047-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound assessment of the spring ligament complex

Abstract: This study was conducted to document the normal ultrasound anatomy of the spring ligament in asymptomatic subjects and to prospectively determine the frequency of ultrasound abnormality of the spring ligament in patients with suspected posterior tibial tendinopathy. The superomedial calcaneonavicular ligament (CNL) of 10 healthy volunteers was examined by ultrasound. Nineteen patients with a clinical diagnosis of suspected posterior tibial tendinopathy and/or chronic pain along the course of the tendon were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…It is challenging to assess the spring ligament clinically, so imaging is important to its evaluation. With US, only the superomedial bundle can be evaluated reliably, and it is best visualized in a sagittal oblique plane parallel to the ligament (59). All components of the spring ligament are well delineated at high-field MRI.…”
Section: Spring Ligamentmentioning
confidence: 99%
“…It is challenging to assess the spring ligament clinically, so imaging is important to its evaluation. With US, only the superomedial bundle can be evaluated reliably, and it is best visualized in a sagittal oblique plane parallel to the ligament (59). All components of the spring ligament are well delineated at high-field MRI.…”
Section: Spring Ligamentmentioning
confidence: 99%
“…13 MRI is able to detect the spectrum of early partial tendon tear and complete tear. 41 The superomedial component of spring ligament that blends with the deltoid ligament is often noted to have ruptured in patients with AAFD. MRI is able to show high intrinsic soft tissue contrast.…”
Section: Discussionmentioning
confidence: 99%
“…9 Mansour et al 41 demonstrated an abnormal spring ligament measuring 5.1 mm and 6.1 mm at the proximal and distal sites, respectively; the same authors also observed in their studies that five of the nineteen patients were found to have increased power Doppler of the spring ligament when it was deficient. 41 The superomedial component of spring ligament that blends with the deltoid ligament is often noted to have ruptured in patients with AAFD. 42 There are three types of spring ligament tear; type I, partial tears either at the sustentaculum tali or navicular insertion as single or multiple small delamination tears within the mid-substance, which is demonstrated in case 4; type II, obvious evidence of ligament laxity with or without the finding of a tear, demonstrated in cases 2, 5, 6, 7 and 8; and type III correlated to case 3, complete rupture of the ligament.…”
Section: Discussionmentioning
confidence: 99%
“…With the foot rotated externally with dorsal extension, the transducer is initially placed in the transverse plane inferior to the medial malleolus and over the sustentaculum tali. The transducer is then moved anteriorly and angled superiorly toward the talar head, allowing the superomedial calcaneonavicular ligament to be identified in long axis (Figure ) . The medioplantar and inferoplantar calcaneonavicular ligaments are not consistently visualized on US because of their deep and complex course .…”
Section: Spring Ligament Complex (Calcaneonavicular Ligament)mentioning
confidence: 99%
“…The transducer is then moved anteriorly and angled superiorly toward the talar head, allowing the superomedial calcaneonavicular ligament to be identified in long axis (Figure 15). 27 The medioplantar and inferoplantar calcaneonavicular ligaments are not consistently visualized on US because of their deep and complex course. 8 The superomedial calcaneonavicular ligament thickness has been described as 1.9 to 4.7 mm.…”
Section: Spring Ligament Complex (Calcaneonavicular Ligament)mentioning
confidence: 99%